Ethylene‐removing packaging: Basis for development and latest advances. Issue 6 (20th September 2020) - Awalgaonkar, Gauri; Beaudry, Randolph; Almenar, Eva
Abstract: Produce is rapidly gaining market share worldwide. Ethylene is a gas molecule that causes detrimental changes in produce. Thus, it is crucial to reduce surrounding ethylene besides inhibiting ethylene biosynthesis to extend produce shelf life and reduce food waste. Ethylene‐removing packaging (ERP) can reduce ethylene concentration surrounding produce during transportation and commercialization. The information found in the literature on the topic is minimal and incomplete compared to other types of active packaging. It focuses on compounds with an ethylene‐removing capacity rather than on the packaging technology per se. The goal of this literature review is to compile and discuss information from peer‐reviewed scientific papers and industry websites on the basics on ERP and on recent developments that can be used to build on and to advance this type of active packaging. This review first focuses on factors needed to design effective ERP including produce characteristics, in‐package composition, material properties and their changes after compounding, remover properties, integration techniques, and environment. Next, this review presents a classification for ERP and provides a detailed analysis of various ethylene‐removing compounds including their mechanisms of action, integration techniques, impacts on produce shelf life, advantages and drawbacks including safety, commercial applications, and combinations with other shelf‐life extending technologies. Some ERP designs are more promising to extend produce shelf life than others, but there is still room for further research to advance this packaging strategy. Specific needs include investigation of ethylene removal for fresh‐cut produce and exploring different integration techniques and materials for such integration.